Cardiac Function in Uncomplicated Type 2 Diabetes Mellitus - Agrawal, Bimal K; Jain, Parul; Marwaha, Saurabh; Goel, Richa; Kumar, Himanshu D; Jagdish, - (Bangladesh Journal of Medical Science, 2019)
Objective: Diabetic cardiomyopathy (DC) is a myocardial disease characterized by myocyte hypertrophy, interstitial fibrosis, protein glycosylation and intra-myocardial micro-angiopathy due to prolonged exposure of myocardial tissues to hyperglycemia in diabetes mellitus (DM) patients. Alteration in cardiac function can be non-invasively assessed via echocardiography. The early recognition of cardiac dysfunction can prevent the symptomatic heart failure in DM patients. The study aimed at evaluating cardiac function in uncomplicated type 2 diabetes mellitus. Materials And Methods: Sixty Type 2 DM patients without any feature of the coronary arterial disease (CAD), hypertension, nephropathy and respiratory illness were enrolled in the study and compared with the sixty age matched healthy controls. Echocardiographic assessment was done in all subjects to evaluate the cardiac function. Results: Diastolic dysfunction was more common in diabetic patients when compared with normal healthy population. Systolic dysfunction progresses with age of the diabetic patient. Conclusion: Echocardiography is a simple noninvasive cost effective test for detecting cardiac dysfunction in Type 2 DM patients and should be applied to detect early Left ventricular(LV) dysfunction so that corrective measures may be initiated early and cardiac functions may be preserved for long. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.211-215